New York School (the); the painters and sculptors of the fifties. - Sandler, Irving (New York : Harper & Row, 1978)
Blaine, Nell ; Briggs, Ernest ; Chamberlain, John ; Diebenkorn, Richard ; Dine, Jim ; Dugmore, Edward ; Francis, Sam ; Frankenthaler, Helen ; Freilicher, Jane ; Goldberg, Michael ; Goodnough, Robert ; Grooms, Red ; Hartigan, Grace ; Held, Al ; Johns, Jasper ; Johnson, Lester ; Kaprow, Allan ; Katz, Alex ; Kelly, Ellsworth ; De Kooning, Elaine ; Leslie, Alfred ; Louis, Morris ; Mitchell, Joan ; Müller, Jan ; Noland, Kenneth ; Oldenburg, Claes ; Parker, Raymond ; Pearlstein, Philip ; Porter, Fairfield ; Rauschenberg, Robert ; Resnick, Milton ; Rivers, Larry ; Schueler, Jon ; Segal, George ; Smith, Leon Polk ; Stankiewicz, Richard ; Stella, Frank ; Suvero, Mark di ; Whitman, Robert
boek